Liturgical Legislations of the Council of Nicaea: Background and Reception - Pallikunnel, Geo (Asian Horizons, 2025)
The Council of Nicaea (325 AD), primarily known for resolving the Arian controversy and formulating the Christological faith of the early Church, also enacted significant liturgical legislations that shaped Christian worship. These decrees addressed doctrinal and practical concerns, reinforcing the principle of lex orandi, lex credendi—how the Church worships reflects what it believes. Key liturgical decisions included the standardization of Easter’s date, separating it from the Jewish Passover to emphasize Christ’s Resurrection, and prohibiting kneeling on Sundays and during Easter season (Canon 20) to reflect the joy of resurrection, the key Christological mystery. The council also regulated ecclesiastical order, clarifying the roles of bishops, priests, and deacons (Canons 6, 18), and established pastoral guidelines for Eucharistic discipline (Canon 13) and the readmission of lapsed believers (Canon 14). The reception of these legislations varied across Christian traditions, with the Byzantine Church adhering closely, while the Latin West and Eastern churches adapted them within local practices. The Easter date controversy persists today despite Nicaea’s efforts, highlighting ongoing ecumenical challenges. The council’s liturgical reforms remain relevant, demonstrating the enduring link between orthodox faith and worship. Nicaea’s legacy underscores that liturgy is not merely ritual but a vital expression of the Church’s faith and theological identity.